Time Limit Exception Provisions for Heirs of Auction Buyers in Voluntary Auctions of Immovable Property - Ismawan, Almira Thalysa; Sihabudin, Sihabudin; Rachman, Rino Arief (IJBLE Scientific Publications Community Inc., 2024)
This study is motivated by the incompleteness of the norms in Article 88 Paragraph (2) of Minister of Finance Regulation No. 122 of 2023 regarding the exception of the 5 working days time limit from the auction for heirs of individual voluntary auction buyers. The aims of this study are to analyze the urgency of establishing time limit exclusion arrangements for the heirs of individual voluntary auction buyers for immovable property. Furthermore, this study was of a normative juridical type using a statute approach and conceptual approach. The results of this study shows that upon death, rights and obligations transfer to heirs. So that the heirs must settle auction payments within 5 working days and pay BPHTB. Thus, necessary to add a clause to Article 88 Paragraph (2) of Minister of Finance Regulation No. 122 of 2023 ensures legal certainty and justice for heirs of individual voluntary auction buyers.